2016
DOI: 10.1182/blood.v128.22.158.158
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activation in a Murine Model of Sickle Cell Disease: Inhibition of Vaso-Occlusion By Blocking C5 Activation

Abstract: Introduction Innate immune complement activation may contribute to sickle cell disease (SCD) pathogenesis. The alternative complement pathway is abnormally activated in SCD and is additionally activated by phosphatidylserine (PS) on the outer leaflet of SS-red blood cells (SS-RBC). PS on the surface of SS-RBC and activated platelets accelerates the assembly of prothrombinase complexes leading to generation of thrombin, which can cleave circulating C5 protein into two biologically active fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Indeed, P-sel-inhibitor crizanlizumab was associated with a lower frequency of sickle cell-related pain crises in patients (51). Complement activation is also observed in SCD (52)(53)(54), and its blockade prevents stasis in a mouse model (55). Therefore, we postulate that a P-sel blockade will reduce complement activation on endothelium of SCD patients and therefore the complement-mediated endothelial lesions.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, P-sel-inhibitor crizanlizumab was associated with a lower frequency of sickle cell-related pain crises in patients (51). Complement activation is also observed in SCD (52)(53)(54), and its blockade prevents stasis in a mouse model (55). Therefore, we postulate that a P-sel blockade will reduce complement activation on endothelium of SCD patients and therefore the complement-mediated endothelial lesions.…”
Section: Discussionmentioning
confidence: 93%
“…PS on the surface of SS-RBCs and activated platelets accelerates the assembly of prothrombinase complexes, leading to thrombin generation, which can generate biologically active C3/C5 fragments, including the anaphylatoxins C3a/C5a [193, 200]. C3b opsonizes SS-RBC and C5b initiates the formation of membrane attack complexes on SS-RBC that respectively increase their susceptibility to extravascular clearance and intravascular lysis [201, 202]. Arumugam et al demonstrated that genetically reducing prothrombin levels limits inflammation, endothelial cell activation, and end-organ damage in SCD mice [154].…”
Section: Chronic Inflammatory Mechanisms In Sickle Cell Diseasementioning
confidence: 99%
“…15–22 Preliminary data from a mouse model of SCD suggest a possible role for complement activation in the generation of vaso-occlusive crises, as an additional disease mechanism contributing to the severity of acute clinical manifestations related to SCD. 23,24…”
Section: Introductionmentioning
confidence: 99%